The shadow of God Kant, Hegel, and the passage from heaven to history - Rosen, Michael, 1952- (The Belknap Press of Harvard University Press, 2022)
"Michael Rosen shows how the redemptive hope of religion became the redemptive hope of historical progress. This was the heart of German Idealism: purpose lay not in God's judgment but in worldly projects; freedom required not being subject to arbitrary authority, human or divine. Yet purpose and freedom never shed their theistic structure"--